Resistance of cowpea genotypes to the cowpea black aphid - da Silva, Jefté Ferreira; Bleicher, Ervino (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate cowpea (Vigna unguiculata) genotypes for resistance to the black aphid (Aphis craccivora). Experiments, with and without choice, were performed in the greenhouse, at the Universidade Federal do Ceará, Fortaleza, Brazil. The experimental design was a randomized complete block with twenty treatments represented by the genotypes 421-07-44, Chumbinho, Zebu, EPACE 10, Frade Preto, Inhumã, João Paulo II, Manteiguinha Maranhão, Pitiúba, Quarenta Dias, Seridó, Sete Semanas, TVu 1037, TVu 1888, TVu 310, TVu 36, TVu 408P2, TVu 410 and VITA 7. The genotypes TVu 408P2, TVu 1037 and TVu 410 were less preferred by adults and nymphs of the black aphid in both assays. The genotypes TVu 408P2, TVu 410, TVu 36 and TVu 1037 probably presented antibiosis or antixenosis resistance. The genotype 421-07-44 was susceptible the black aphid.